possible Permian suture in the Lhasa Block, Tibet: Evidence from eclogites and probable ophiolite - Songyong, Cheng; Jingsui, Yang; Tianfu, Li; Xiangzhen, Xu; Zhaoli, Li; Yufeng, Ren (Himalayan Journal of Sciences, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> DOI = 10.3126/hjs.v5i7.1334 Himalayan Journal of Sciences Vol.5(7) (Special Issue) 2008 p.155